A study on eclampsia and its maternal and perinatal outcome - Kamat, Devika J.; Pednecar, Guruprasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia is one of the major causes of maternal and perinatal mortality in India. Here authors present a prospective study which was conducted in a tertiary health centre to study the cases of eclampsia, the mode of presentation and the maternal and perinatal outcomes. Methods: A total 95 women were diagnosed as eclampsia during the period of 2 years. Various parameters and their effects on maternal and perinatal morbidity and mortality were studied. Maternal outcomes were assessed based on parameters like antenatal care received, mode of delivery, complications associated with eclampsia. Perinatal outcomes were noted depending upon the period of gestation, NICU admission, stillbirths and neonatal deaths. Results: Authors found the incidence of eclampsia to be 0.9%. 52.7% women had irregular antenatal follow up at any nearby health centre. A total 76.8% women had antepartum eclampsia. 56.8% delivered by caesarean section while 7.4% required operative vaginal delivery. 61.1% women delivered within 10 hours of onset of convulsion. Authors had 02 deaths in the study group, one due to ARDS with DIC and the other attributed to pulmonary oedema. There were 51.6% preterm deliveries. 21 neonates required NICU admission with 5 neonatal deaths and 11 stillbirths. Conclusions: Due to inadequate antenatal care, most of the cases of pre-eclampsia go unnoticed increasing the referrals to tertiary care centre for intensive care. Thus, it is necessary to emphasise on timely interventions and availability of blood bank, ICU and NICU facilities at the closest referral centre for better maternal and perinatal outcome.